Optimization of Organotypic Cultures of Mouse Spleen for Staining and Functional Assays - Finetti, Francesca; Capitani, Nagaja; Manganaro, Noemi; Tatangelo, Vanessa; Libonati, Francesca; Panattoni, Giulia; Calaresu, Ivo; Ballerini, Laura; Baldari, Cosima T.; Patrussi, Laura (Frontiers in Immunology, 2020)
By preserving cell viability and three-dimensional localization, organotypic culture stands out among the newest frontiers of cell culture. It has been successfully employed for the study of diseases among which neoplasias, where tumoral cells take advantage of the surrounding stroma to promote their own proliferation and survival. Organotypic culture acquires major importance in the context of the immune system, whose cells cross-talk in a complex and dynamic fashion to elicit productive responses. However, organotypic culture has been as yet poorly developed for and applied to primary and secondary lymphoid organs. Here we describe in detail the development of a protocol suitable for the efficient cutting of mouse spleen, which overcomes technical difficulties related to the peculiar organ texture, and for optimized organotypic culture of spleen slices. Moreover, we used microscopy, immunofluorescence, flow cytometry, and qRT-PCR to demonstrate that the majority of cells residing in spleen slices remain alive and maintain their original location in the organ architecture for several days after cutting. The development of this protocol represents a significant technical improvement in the study of the lymphoid microenvironment in both physiological and pathological conditions involving the immune system.